Effectiveness and Cost-Effectiveness of a Stratified Blended Physiotherapy Intervention Compared With Face-to-Face Physiotherapy in Patients With Nonspecific Low Back Pain: Cluster Randomized Controlled Trial - Tjarco Koppenaal; Johanna M van Dongen; Corelien JJ Kloek; Remco M Arensman; Cindy Veenhof; Martijn F Pisters; Raymond WJG Ostelo (JMIR Publications, 2023)
BackgroundNonspecific low back pain (LBP) is a leading contributor to disability worldwide, and its socioeconomic burden is substantial. Self-management support is an important recommendation in clinical guidelines for the physiotherapy treatment of patients with LBP and may support cost-effective management. However, providing adequate individually tailored self-management support is difficult. The integration of web-based applications into face-to-face care (ie, blended care) seems promising to optimize tailored treatment and enhance patients' self-management and, consequently, may reduce LBP-related costs. ObjectiveWe aimed to evaluate the long-term effectiveness and cost-effectiveness of stratified blended physiotherapy (e-Exercise LBP) compared with face-to-face physiotherapy in patients with nonspecific LBP. MethodsAn economic evaluation was conducted alongside a prospective, multicenter, cluster randomized controlled trial in primary care physiotherapy. Patients with nonspecific LBP were treated with either stratified blended physiotherapy (e-Exercise LBP) (n=104) or face-to-face physiotherapy (n=104). The content of both interventions was based on the Dutch physiotherapy guidelines for nonspecific LBP. Blended physiotherapy was stratified according to the patients' risk of developing persistent LBP using the STarT Back Screening Tool. The primary clinical outcome was physical functioning (Oswestry Disability Index version 2.1a). For the economic evaluation, quality-adjusted life years (QALYs; EQ-5D-5L) and physical functioning were the primary outcomes. Secondary clinical outcomes included fear avoidance beliefs and self-reported adherence. Costs were measured from societal and health care perspectives using self-report questionnaires. Effectiveness was estimated using linear mixed models. Seemingly unrelated regression analyses were conducted to estimate total cost and effect differences for the economic evaluation. ResultsNeither clinically relevant nor statistically substantial differences were found between stratified blended physiotherapy and face-to-face physiotherapy regarding physical functioning (mean difference [MD] −1.1, 95% CI −3.9 to 1.7) and QALYs (MD 0.026, 95% CI −0.020 to 0.072) over 12 months. Regarding the secondary outcomes, fear avoidance beliefs showed a statistically significant improvement in favor of stratified blended physiotherapy (MD −4.3, 95% CI −7.3 to −1.3). Societal and health care costs were higher for stratified blended physiotherapy than for face-to-face physiotherapy, but the differences were not statistically significant (societal: €972 [US $1027], 95% CI −€1090 to €3264 [US -$1151 to $3448]; health care: €73 [US $77], 95% CI −€59 to €225 [US -$62 to $238]). Among the disaggregated cost categories, only unpaid productivity costs were significantly higher for stratified blended physiotherapy. From both perspectives, a considerable amount of money must be paid per additional QALY or 1-point improvement in physical functioning to reach a relatively low to moderate probability (ie, 0.23-0.81) of stratified blended physiotherapy being cost-effective compared with face-to-face physiotherapy. ConclusionsThe stratified blended physiotherapy intervention e-Exercise LBP is neither more effective for improving physical functioning nor more cost-effective from societal or health care perspectives compared with face-to-face physiotherapy for patients with nonspecific LBP. Trial RegistrationISRCTN 94074203; https://www.isrctn.com/ISRCTN94074203 International Registered Report Identifier (IRRID)RR2-10.1186/s12891-020-3174-z